Research on the energy characteristics of the turning region in the cavitation performance curve of an axial flow pump based on energy flow density and entropy production - Lei Yu; Li Cheng; Weigao Sheng; Shuaihao Lei; Wentao Xu; Jiantao Shen (Engineering Applications of Computational Fluid Mechanics)
Cavitation significantly impacts the performance and stability of axial flow pumps, yet the underlying mechanisms driving head rise in the cavitation curve remain inadequately understood. This study provides a novel exploration of internal flow dynamics and energy dissipation in the turning region of the cavitation curve, where head rises. By integrating vortex dynamics and entropy production theory, the intricate interplay between cavitation-induced flow separation and energy loss is revealed. Numerical simulations, validated by experimental data, are employed to analyze energy flow density fluctuations caused by pressure pulsations across different pump regions. The results uncover a critical link between abrupt energy flow density variations and localised high-energy dissipation, which originate from flow separation on the suction side of the impeller blades. Specifically, at the cavitation coefficient where head rise begins, flow separation emerges around the mid-tip region due to cavitation effects at the blade tip and suction surface. As cavitation intensifies and head reaches its peak, the separation zone progressively expands from tip to hub, further amplifying energy dissipation. Beyond this point, excessive cavitation triggers a rapid head drop, shifting the separation zone toward the trailing edge and enhancing the development of the tip separation leakage vortex. This study not only elucidates the physical mechanisms governing head rise under cavitation but also establishes a deeper connection between energy loss and cavitation dynamics, offering valuable insights for optimising axial flow pump performance in cavitating conditions.